The relationship between self-esteem and aggressive behavior among Chinese adolescents: A moderated chain mediation model - Hu, Yuanyan; Cai, Yi; Wang, Rui; Gan, Yihan; He, Nianqin (Frontiers in Psychology, 2023)
This study aimed to examine the relationship between adolescent self-esteem and aggressive behavior. Specifically, a moderated chain mediation model was developed to investigate the mediating role of jealousy and self-control and the moderating role of gender. Data were collected from 652 Chinese adolescents who completed the Self-Esteem Scale, Self-Report Jealousy Scale, Self-Control Scale and Aggressive Behavior Questionnaire. Results showed that adolescent self-esteem may significantly negatively affect aggressive behavior by mediating with jealousy and self-control. Moreover, gender possibly moderates the serial mediating effect of jealousy and self-control between adolescent self-esteem and aggressive behavior. The results have important theoretical and practical implications in that these reveal the influencing factors of adolescent aggressive behavior and the pathways to reduce such behavior.